Onboard Instability Correction of a Flying Wing Unmanned Aerial Vehicle - Lucena, Alysson; Gonçalves, Luiz (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2020: Anais do XII Simpósio Brasileiro de Robótica e XVII Simpósio Latino Americano de Robótica, 2020)
The development of unmanned aerial vehicles (UAVs) has undergone extensive development in recent years, responsible for reducing operational and manufacturing costs and also preserving the pilot in missions that present risks. The pursuit of greater ﬂight autonomy in fixed wing UAVs is aimed at the aircraft development, which can generate the highest possible lift with the lowest weight and drag. In this context the ﬂying wing is considered the ideal aircraft, but it has instability during ﬂight due to the absence of warping. With the use of a computerized system for corrections, a 1.20m wingspan UAV with ﬂexible characteristics is proposed and developed in this work, considering all its stages: aerodynamic analysis, construction and configuration, remotely controlled tests, and autonomous mission with image acquisition. As a result of its operation, we could perform both remote controlled and autonomous ﬂights acquiring images, which demonstrates the effectiveness of the project and used embedded systems.